Pengaruh Promosi, Ekuitas Merek, dan Kualitas Produk terhadap Keputusan Pembelian melalui Aplikasi McDonald’s - Cindy Octavian; Bambang Nur Supriyanto (LPPM Universitas Asa Indonesia, 2023)
The purpose of this study is to seek the influence of promotions, brand equity, and product quality on purchasing decisions. The data collection was carried out by spreading the questionnaire to 130 McDonald's Application user respondents. Incidental sampling is used as a sampling method and is processed using the SmartPLS 2.3 application. The results of this study show that promotions have a significant effect on purchasing decisions, brand equity has a significant effect on purchasing decisions, and product quality has no significant effect on purchasing decisions.